Dynamic Modeling Analysis of Paddle Aerator Performance on Litopenaeus vanamei Ponds - Ariadi, Heri; Linayati, Linayati; Mujtahidah, Tholibah (International Journal of Social Science, Education, Communication and Economics, 2025)
Paddle aerators are an important tool in intensive shrimp farming. The purpose of this study is to determine the performance and electrical power consumption of paddle aerators based on the results of dynamic modelling analysis. This study uses causal ex-pose facto design concept with data analysis using dynamic modelling system. The results showed the salinity levels of pond 1 20-27 gr/L and pond 2 31-33 gr/L, pH pond 1 7.9-9.0 and pond 2 8.1-8.3, DO concentration pond 1 4.43-6.93 mg/L and pond 2 4.72-5.99 mg/L, temperature pond 1 27.15-31.400C with a brightness of 43 cm and pond 2 ranging from 27.50-29.850C with a brightness of 49 cm. From the calculation of the level of oxygen production paddle aerator power 1 HP produces oxygen average 2.12 mgO2 / hour (1.68-2.89 mgO2 / hour) with gas pressure 10.31-16.00 mmHg and paddle aerator power 2 HP produces oxygen average 3.20 mgO2 / hour (2.82-3.65 mgO2 / hour) with gas pressure 10.05-14.56 mmHg. From the accumulated results, the electrical load power required for pond 1 is about 6.83-10.38 kW and pond 2 is about 6.59-7.71 kW. The performance of 1 HP paddle aerator is more effective than 2 HP paddle aerator 4 pieces. The results of dynamic model analysis estimated the level of dissolved oxygen production by paddle aerators during one cultivation cycle ranged from 1-2.70 mgO2/hours and 1-2.75 mgO2/hours with a rotational speed of 0-30 rpm/s and power requirements of 8-10 kW. The conclusion from the results of this study is that the use of 1 HP paddle aerators in large quantities is proven to be more effective and based on the results of dynamic modelling system analysis, it is shown that the performance of DO production by paddle aerators will stagnate at week ten of the cultivation period, with increasing electrical power requirements.